Pengaruh Pemberian Reward Sticker Emoticon Terhadap Percaya Diri Anak Usia 5-6 Tahun Di TK Sentuhan Kasih Abadi Tarutung - Hana Sitorus; Endang Junita Sinaga; Julita Herawati P (Journal of Creative Student Research, 2023)
The aim of this research is to determine the effect of giving emoticon sticker rewards on the self-confidence of children aged 5-6 years. The method used in this research is a quantitative research method of the pre-experimental design type in the form of "One Shot Case Study". The population was all children aged 5-6 years (group B) at the Tarutung Touch of Eternal Love Kindergarten, totaling 67 people and a sample of 18 children was determined using a non-probability sampling technique, purposive sampling type. Data was collected using a 15-item positive closed questionnaire. The results of data analysis show that there is an Emoticon Sticker Reward given to the self-confidence of children aged 5-6 years at the Tarutung Touch of Eternal Love Kindergarten: 1) Test analysis requirements: a) positive relationship test obtained by the value rxy = 0.588 > rtable(a=0, 05,n=18) = 0.468, thus it is known that there is a positive relationship between variable )= 2.120, thus there is a significant relationship between variable "+1.11X. Thus Ha is accepted and H0 is rejected.